Gender Differences in Cyberbullying Victimization - Abd Ajis, Muhammad Khairul Annuar; Kasim, Nur Muneerah; Ghazali, Fitty Ayunee (Selangor Humaniora Review, 2022)
This study is proposed after seeing the rapid use of social media as a medium to bully each other regardless of male or female, which is feared to invite prejudice, mutual hatred, and hostility. The public is concerned about the content of messages and comments that are misleading, slanderous, and disgraceful. Therefore, this study could see gender differences that invite implications for cyberbullying among university students. The study involves a sample of 150 respondents from public and private university students in Malaysia. Data was collected using an online survey by filling out the Google Form based on a self-administered survey questionnaire. The data obtained were analyzed using the software Statistical Packages for Social Sciences (SPSS) version 21.0. and Mann–Whitney U-test to test the hypothesis in examining cyberbullying victimization based on gender differences. A Mann-Whitney test showed no significant differences between the scores of cyberbullying victimization and gender differences. The male group (n=18) and female group (n=122) is not statistically significant, Mann-Whitney U (1510.500) = -0.959, ρ = 0.338. The finding from this study is necessary to create awareness among university management, parents, and peers to exercise their role in protecting young adults from being a cyberbullying victim.